Food science and nutrition breakthroughs in research and practice (Medical Information Science Reference, 2018)
"This book is an innovative reference source for the latest academic material on how dietary nutrition can impact people's lives, prevent disease, and maintain an overall healthier lifestyle. Highlighting a range of topics such as health preservation, functional foods, and herbal remedies"--Provided by publisher